Information and Communication Technologies (ICTs) Adoption by MSMEs and Local Poverty: An Empirical Evidence from Indonesia - Hanggraeni, Dewi (Jurnal Keuangan dan Perbankan, 2021)
This paper aims to examine a relationship between the adoption of Information and Communication Technologies (ICTs) by Micro, Small, and Medium Enterprises (MSMEs) and local poverty in Indonesia. Previous literature has shown that the adoption of ICTs is a significant catalyst to increasing a nation’s productivity from a macroeconomic perspective. This has imposed a new debate among researchers whether the adoption of ICTs can contribute to a more specific economic development goal: reducing poverty. Some researchers argue that the means of a broader economic development can be obtained through the informal sectors, MSMEs. Therefore, this paper argues that in order to find a more satisfactory result, the role of ICTs adoption in reducing poverty needs to be examined from within a more specific economic agent—the MSMEs. To test the hypothesis, we run OLS regression models with province and year fixed effects on our MSMEs survey data and local poverty measures. The results show a robust, negative relationship between the adoption of ICTs by MSMEs and the number of poor populations in the corresponding region, controlling other factors. DOI : https://doi.org/10.26905/jkdp.v25i2.5343